The Sustainable Development Goals Report 2021 - United Nations Department of Economic; Social Affairs (United Nations, 2021)
The annual Sustainable Development Goals Report provides an overview of the world’s implementation efforts to date, highlighting areas of progress and areas where more action needs to be taken to ensure no one is left behind. While advances have been made in some areas, monumental challenges remain. The evidence and data spotlight areas that require urgent attention and more rapid progress to realize the 2030 Agenda’s far-reaching vision. This sixth edition of the report also looks at the impact of COVID-19 in reaching the Goals.